Hukum Attakhattî (Melangkahi Pundak Jamaah) Ketika Khutbah Hari Jum’at Menurut Perspektif Mazhab Hanafi Dan Mazhab Syafi’i - Ismail, Ismail; Sa'adah, Sa'adah; Muttaqin, Zainal (Sharia Journal and Education Center Publishing, 2024)
Abstract Friday is a special day for Muslims, explained by Ibn Kathir as a day of gathering. On this day, the Friday prayer (Salat al-Jumu'ah) is performed, consisting of two obligatory units (rak'ahs) following two sermons (khutbahs), with specific conditions and pillars that must be met for the prayer to be valid according to Islamic law. One important aspect discussed in the context of Friday prayer is the prohibition of